Taxonomia e macroanatomia de Anachis (Anachis) lyrata (Sowerby, 1832), Anachis (Costoanachis) sertulariarum (D'Orbigny, 1839) e Anachis (Parvanachis) obesa (C. B. Adams, 1845) (Mollusca, Gastropoda, Columbellidae) - Sá, Magali Romero (1986)
Anachis (Anachis) lyrata (Sowerby, 1832), Anachis (Costoanachis) sertulariarum (d'Orbigny, 1832), and Anachis (Parvanachis] obesa (C. B. Adams, 1845] were investigated in relation to their taxonomy, conchology and macroanatomy. The purpose of the study was to provide a comprehensive characterization of the species, in order to contribute towards the elucidation of the taxonomic problems involving the group below the genus level.